Maggie's miracle : a novel - Kingsbury, Karen (Kingsbury, Karen. Red gloves series., 2003)
Megan Wright spent just a week with him the summer of their 14th year. But despite a lifetime of heartache and bad choices, she never let go of young Kade's magical definition of love. After college Megan settled for a relationship of convenience. Now it's been two years since her husband's death and she is a high-powered attorney, looking for help with her lonely young son. Across town, Casey Cummins is still dealing with the three-year-old tragic loss of his wife. His search for meaning and hope leads him to contact the Manhattan Children's Organization, who connect him with a fatherless child. Now life is suddenly taking a series of unusual twists. How could Megan know that the teenage boy from all those years ago actually kept his promise? Or that the miracle she prayed for as a girl is only a breath away? The prayers of her little boy are about to be answered, and in a strange and mysterious way that only heaven in all its glory could've brought about.